Low pressure plasma focus for deuteron Beam generation / Lim Lian Kuang - Lim , Lian Kuang (2017)
The thesis presented an experimental investigations performed on the radiation (ion beam, neutrons and X-rays) emitted from a 2.7 kJ plasma focus device. With the aim to optimize for ion beam emission, the system has been modified with long electrode configuration operated at low pressures. Work has been carried out to find the best parameters while matching characteristic time of plasma focus. Diagnostics techniques including Faraday cup, biased ion collector and solid state nuclear track detectors were employed for the study of ion beams emission in terms of beam energies, their fluence (ions/m2), number of ions and angular distribution of the emissions. Lee model code was configured to according to the system parameters and generate outputs at the experimental conditions. The results were compared with the experimental data. The study suggested that multiple current dips and prolong duration in the drop of discharge current signals corresponded to anomalous resistance played an important role in the ion beam emission. Significant ion beam emission with good reproducibility was obtained at operating pressure in the range of 0.1 – 0.5 mbar. The best condition is 0.2 mbar deuterium filling. Ion beams with energies in the range of 18 – 350 keV have been measured, while the discharge voltage was 13.5 kV. Ion beam fluence is estimated in the order of 1015 ions/m2. The emission was highly anisotropic in the forward direction and spread out to about 30o. The density of ion tracks measured to be 6.3 x 1010 ions/m2 while in the velocity space they are in Maxwell-Boltzmann distribution. Electron temperature of the deuterium plasma was estimated as 3 – 5 keV. Correlation between the radiation emissions and pinch dynamics gave a clear picture that the ion beams were emitted at different instances during the pinch phase.